THE IMPLEMENTATION OF BALINESE FOLKLORE-BASED REFLECTIVE STORYTELLING TO IMPROVE SPEAKING COMPETENCY - I Komang Budiarta,; Ni Wayan Krismayani,; Ni Made Wersi Murtini, (SPHOTA: Jurnal Linguistik dan Sastra, 2016)
ABSTRACT Speaking competency is one of the necessary language competencies to be mastered by the students. In fact, the teaching learning process on Speaking Course became one of the frightening courses, and it sometimes decreased the students’ self-confidence because the implementation of inappropriate teaching technique. In the present study, Balinese Folklores-based Reflective Storytelling as the teaching model was implemented to deal with the problem. The present classroom action research was intended to figure out how speaking competency can be improved through Balinese Folklores-based Reflective Storytelling and how the students respond the implementation of Balinese Folklores-based Reflective Storytelling. The third semester students of English Education Study Program, Faculty of Teacher Training and Education, Mahasaraswati Denpasar University consisting of 71 students were chosen as the subjects of the study. The findings clearly showed that the speaking competency of the subjects can be improved through the implementation of Balinese Folklores-based Reflective Storytelling. In addition, the subjects also responded positively the implementation of Balinese Folklores-based Reflective Storytelling in teaching speaking. Keywords: reflective storytelling, Balinese folklores, and speaking competency.